Mapeamento da ilha da Trindade, Atlântico Sul - Patricio, Ramon Lourenço [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
The area chosen for this study is the island of Trinidade, which is located 1167 km off the Brazilian coast, in parallel Victory at 20 ° 30'S and 29 º 19'W, being the most easterly point of our continent. The isolation of oceanic island of Trinidade leaves no noticeable that she is part of a large submarine volcanic chain oriented east-west lineament known as Vitória- Trindade. Along with the island of Martin Vaz, who is Federal Territory is administered by the Navy of Brazil. Both correspond to Source alkaline volcanic islands. The area of the island of Trinidad has approximately 10 km2. Geologically consisting ankaratritic spills, spills tannbuschiticos, volcanic tuff spills analcite-ankaratrite, phonolite spills, spills nefelinite, pyroclastics, spills grazinite, tinguaitos, olivine-analcitito, calcarenite dunes and wind according to Almeida (1961). The island has its base on the ocean floor, at 5,800 m depth. It is the only place still recognizes preserved volcanic necks and plugs, as well as remnants of a volcano in Brazil. Magmatism occurred here a sodium alkali-silica subsaturated where his wrist was last 50,000 years according to Almeida (1961). It is a place with restricted access due to their distance from the coast, his contribution and hard to be an exclusive area of the Navy. On the island with peaks occur up to 620 meters high, and its rugged mountainous terrain and difficult access to very specific points, as the peak of Desire, peak Fazendinha, Monument and other points on the island. Because of its location far from the coast, its small infrastructure, difficulty of landing and restricted access by sea, the island of Trinidad offers no possibility of tourism, being a military outpost, and scientific basis of great importance, which conduct research in area of marine biology, oceanography, geology and others

A área escolhida para o presente trabalho é a Ilha da Trindade, que está localizada a 1.167 km da costa brasileira, no paralelo de Vitória, a 20º 30’S e 29º 19’W, sendo o ponto mais a leste do nosso continente. O isolamento oceânico da Ilha da Trindade não deixa perceptível que ela é parte de uma grande cadeia vulcânica submarina orientada leste-oeste, conhecido como lineamento Vitória-Trindade. Junto com a ilha de Martin Vaz, constitui Território Federal que é administrado pela Marinha do Brasil. Ambas correspondem a ilhas vulcânicas de origem alcalina. A área da ilha da Trindade possui aproximadamente 10 km2. Geologicamente constituída por derrames ankaratriticos, derrames tannbuschiticos, tufos vulcânicos, derrames de analcita-ankaratrito, derrames de fonólito, derrames de nefelinito, piroclastos, derrames de grazinito, tinguaitos, olivina-analcitito, calcarenitos e dunas eólicas segundo Almeida (1961). A ilha tem sua base sobre o assoalho oceânico, a 5.800 m de profundidade. É o único lugar aonde ainda se reconhecem necks e plugs vulcânicos preservados, bem como resquícios de um vulcão no Brasil. Ocorreu aqui um magmatismo sódico-alcalino subsaturado em sílica, onde seu ultimo pulso foi há 50.000 anos segundo Almeida (1961). É um lugar de acesso restrito, devido a sua distância da costa, seu difícil aporte e ser uma área exclusiva da Marinha. Na ilha ocorrem picos com até 620 metros de altura, seu relevo montanhoso e acidentado dificulta muito o acesso a pontos específicos, como o pico do Desejado, pico da Fazendinha, Monumento e a outros pontos da ilha. Devido sua localização muito longe da costa, sua pequena infraestrutura, dificuldade de desembarque e acesso restrito por mar, a Ilha da Trindade não oferece possibilidade de turismo sendo um posto militar avançado, e uma base científica de grande importância, onde se realizam pesquisas na área de biologia marinha oceanografia, geologia entre outros
Keywords: Geologia; Mapeamento geologico; Petrologia; Vulcões; Trindade, Ilha do (RJ)